Efektivitas Musik Klasik dalam Menurunkan Tingkat Kecemasan pada Mahasiswa: Literature Review - Nurafifah, Wanda; Putri, Rury Eryna (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Anxiety can happen to anyone, including students in college. Anxiety in college students can cause many losses and changes in behavior. For handle that issue, an appropriate is needed to reduce student anxiety; one of the interventions that can be done is classical music therapy, which has been done in several studies. This study aims to see the effectiveness of classical music on anxiety in college students, using the systematic literature review method that analyzes Indonesian and foreign research journals. The data is based on relevant keyword searches on Google Scholar, Publish or Perish 8, Scopus, Research gate, and Taylor & Francis with an initial number of 198 articles based on keywords, in the final result of 11 articles those match the research objective. The analysis of eleven research journals obtained results from eight studies, stating that classical music can reduce anxiety. While the failure in three studies was caused by other factors such as the environment, intervention time, type of music used, frequency of music delivery, ways of listening to music, the room used, different levels of anxiety, dislike of classical music used, and classical music must be combined with other therapies.